The phenomena of electrorheological fluid behavior between two barriers under alternative voltage - Szary, M. L. (Archives of Acoustics, 2004)
Electrorheological (ER) fluids placed between two barriers have the ability to change some of their physical properties like the apparent viscosity and modulus of elasticity when an external electrical field is applied. Early investigations of the sound transmission loss (STL) under DC voltage showed that a normal stress that develops in ER fluid in response to an electrical field has a significant influence on the magnitude of STL. The tangentional (shear) stress had only a negligible effect on the STL. The aim of this study was to investigate the STL using a two-barrier system with ER fluid placed between them, and subjected to alternative voltage. The STL was investigated for various kinds of ER fluids in the presence of the variable alternative electric field density. The results showed that the STL had decreased with the increasing electric field density.